A Dysregulation of the Prolactin/Vasoinhibin Axis Appears to Contribute to Preeclampsia - Lenke, Livia; Martínez de la Escalera, Gonzalo; Clapp, Carmen; Bertsch, Thomas; Triebel, Jakob (Frontiers in Endocrinology, 2020)
Preeclampsia is a hypertensive disorder affecting 3-5 % of all pregnancies. The only curative treatment is delivery of the placenta and the pathophysiology is poorly understood. Studies have demonstrated altered levels of antiangiogenic factors in patients with preeclampsia. One such factor is the antiangiogenic and antivasodilatatory peptide hormone vasoinhibin, which is higher in the circulation, urine, and amniotic fluid of women with preeclampsia. Normal pregnancy is characterized by elevated circulating prolactin and placental lactogen levels, both of which can serve as vasoinhibin precursors when they are enzymatically cleaved. A dysregulation of vasoinhibin generation during preeclampsia is indicated by higher vasoinhibin, prolactin, placental lactogen, and vasoinhibin-generating enzymes levels and activity. The present article integrates known vasoinhibin levels, effects, and signaling mechanisms to the clinical characteristics of preeclampsia to substantiate the notion that vasoinhibin dysregulation can be causally linked to the development of preeclampsia. If this view is demonstrated, assessment of vasoinhibin levels and regulation of its activity could help estimate the risk of preeclampsia and improve its treatment.